Regionalentwicklung unter Schrumpfungsbedingungen: Herausforderung für die Raumplanung in Deutschland - Müller, Bernhard (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Demographic shrinkage is a fact of life both in Germany and in Europe. In both eastern and western Germany it is leading to dramatic changes in spatial structures and throwing up new challenges for spatial planning. It is, however, important to note that shrinkage and growth can often be found side by side and in extremely close proximity to each other. It is against this background that the author explores the changes which need to be made to spatial planning and possible perspectives for steering development. The combination of “top-down” framework steering and “bottom-up” co-ordination — i.e. an incentive-oriented, multi-tiered form of steering — could, it is argued, be a helpful approach to facilitate more differentiated reactions than have previously been possible to the local particularities of development processes.